A Wideband Dual-Polarized Antenna Using Planar Quasi-Open-Sleeve Dipoles for Base Station Applications - Guan-xi Zhang; Li Sun; Bao-hua Sun (International Journal of Antennas and Propagation)
A wideband dual-polarized antenna for WLAN, WiMAX, and LTE base station applications is presented in this paper. The proposed antenna consists of two pairs of orthogonal planar quasi-open-sleeve dipoles along the centerlines, a balanced feeding structure and a square ground plane. The planar quasi-open-sleeve dipole comprises a pair of bowtie-shaped planar dipoles with two parallel curve parasitic elements. The introduced parallel curve parasitic elements change the path of the current of the original bowtie-shaped planar dipoles at high frequencies and hence wideband characteristic is achieved. Two pairs of the planar quasi-open-sleeve dipoles placed orthogonally further broaden the bandwidth of the antenna with dual-polarization characteristics. The proposed antenna achieves a 10-dB return loss bandwidth from 2.32 to 4.03 GHz (53.9% bandwidth) using the planar quasi-open-sleeve dipole structures. The isolation between the two ports remains more than 32 dB in the whole bandwidth. Measured results show that the proposed antenna keeps the cross-polarization under −33 dB and the front-to-back ratio better than 15 dB in the operating band. The antenna has an area of 0.3λ  × 0.3λ at 2.32 GHz making it easy to be extended to an array element.